Analisis Efektivitas Pengendalian Internal Persediaan Obat Rumah Sakit Nahdlatul Ulama Tuban - Hariyanti Hariyanti; Dede Mariyani; Syarifa Ramadayanti (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to determine the effectiveness of internal control of drug inventory at Nahdlatul Ulama Hospital Tuban and to assess the suitability of the implementation of drug supply management with the applicable standards at Nahdlatul Ulama Hospital Tuban. This type of research is descriptive qualitative research. Data collection techniques were carried out by interviews and documentation. The data analysis technique used is stop-or-go sampling. The level of reliability (R%) used is 95% and determines DUPL 5%. Based on data analysis conducted on the effectiveness of internal control of drug supply at the Nahdlatul Ulama Hospital in Tuban and the management of drug supplies at the Nahdlatul Ulama Hospital in Tuban, it has been carried out in accordance with applicable government regulatory standards, it can be seen that: The results of the study on the effectiveness of internal control of drug supplies at the Nahdlatul Ulama Hospital Tuban showed effective results. This can be seen from the test results of the three attributes that did not find any errors in the examination, where 5% AUPL is the same as 5% DUPL. The pharmacy installation at the Nahdlatul Ulama Hospital has implemented the Minister of Health Regulation Number 72 of 2016 on procedures for procurement of pharmaceutical drug supplies, procedures for purchasing pharmaceutical drug supplies, procedures for receiving pharmaceutical drug supplies, procedures for storing pharmaceutical drug supplies, and procedures for distributing pharmaceutical drug supplies.